The Ideal City - Klanten, Robert, 1964-; Stuhler, Elli, ....- (Berlin : Gestalten, 2021)
The city is an always changing human experiment. But in the last half century, it has changed more than ever before - with little sign of slowing down. As this phenomenon takes place, an increasing number of architects, innovators and policy-makers are rethinking the city to make the most of space and resources. This book chronicles the design of urban futures. From apps designed to curb food waste to inventive fresh water infrastructure, The Ideal City explores the many initiatives and experiments, all with the shared goal of making the cities of tomorrow a happier, healthier and more inclusive place to be.
Keywords: Architectuur; Duurzame Stedenbouw; Milieu; Stadsontwikkeling